2018
DOI: 10.3389/fimmu.2018.01724
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke-Induced Pulmonary Inflammation Becomes Systemic by Circulating Extracellular Vesicles Containing Wnt5a and Inflammatory Cytokines

Abstract: Chronic obstructive pulmonary disease (COPD) is a devastating, irreversible pathology affecting millions of people worldwide. Clinical studies show that currently available therapies are insufficient, have no or little effect on elevated comorbidities and on systemic inflammation. To develop alternative therapeutic options, a better understanding of the molecular background of COPD is essential. In the present study, we show that non-canonical and pro-inflammatory Wnt5a is up-regulated by cigarette smoking wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 67 publications
1
35
0
Order By: Relevance
“…In vitro experiments were performed using the TEP1 primary-derived (BALB/c) thymic epithelial cell lines or the A549 human lung epithelial cell line (A549 served as control producer cell compared to TEP1). The Wnt4 over-expressing version of TEP1 and the Wnt5a over-expressing version of A549 were generated via lentiviral transfection linked to the green fluorescent protein (GFP) as published previously (Wnt5a served as control compared to Wnt4) (29, 30). Cells were maintained in DMEM (Dulbecco's Modified Eagle's medium, Lonza) supplemented with 10% FBS (EuroClone), Penicillin-Streptomycin, L-glutamine, Hepes buffer, non-essential amino acids (Lonza), and β-mercapto-ethanol (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments were performed using the TEP1 primary-derived (BALB/c) thymic epithelial cell lines or the A549 human lung epithelial cell line (A549 served as control producer cell compared to TEP1). The Wnt4 over-expressing version of TEP1 and the Wnt5a over-expressing version of A549 were generated via lentiviral transfection linked to the green fluorescent protein (GFP) as published previously (Wnt5a served as control compared to Wnt4) (29, 30). Cells were maintained in DMEM (Dulbecco's Modified Eagle's medium, Lonza) supplemented with 10% FBS (EuroClone), Penicillin-Streptomycin, L-glutamine, Hepes buffer, non-essential amino acids (Lonza), and β-mercapto-ethanol (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The role of lung epithelial cell-derived EVs in the pathogenesis of COPD has also been well reported [120]. Cigarette smoke exposure leads to exaggerated release of exosomes from damaged epithelial cells and promotes emphysema [120]. It has been shown that human bronchial epithelial cells (BEAS-2B) exposed to cigarette smoke demonstrate increased Rab27A-dependent release of EVs [121].…”
Section: Lung Cancermentioning
confidence: 99%
“…In COPD induced by cigarette smoke exposure, alveolar macrophages and alveolar epithelial cells are directly exposed to the toxic components of cigarette smoke [120]. The role of lung epithelial cell-derived EVs in the pathogenesis of COPD has also been well reported [120]. Cigarette smoke exposure leads to exaggerated release of exosomes from damaged epithelial cells and promotes emphysema [120].…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Moreover, further investigation demonstrated that CSE exposure increased Wnt5a expression in conjunction with inflammatory cytokines production in the model of COPD. 9 …”
Section: Introductionmentioning
confidence: 99%